Determinants of Principals’ Performance in Colleges: a Gender based Analysis of Azad Jammu Kashmir - Malik, Mushtaq Haider; Khan, Zaheer Ahmed; Irfan, Mohammad (International Journal of Engineering and Technology, 2018)
The current study examine the determinants of colleges’ principal performance in Azad Jammu Kashmir, Pakistan. For this purpose, current study apply exploratory factor analysis and multiple regression analysis to investigate the determinants of colleges’ principal performance in Azad Jammu Kashmir, Pakistan. The results of gender based analysis regression confirm that management development and supervision have a significant impact on principals’ performance for male subgroup whereas management development, administration and planning have a significant impact on female principals’ performance. The model R-square value for male is 57.5% and 81.1% for female. Therefore it is recommended that these variables are helpful in predicting performance of colleges.